Approximation Properties of a New Class of Beta-Type Szász–Mirakjan Operators - Md. Nasiruzzaman; Rubayyi T. Alqahtani; S. A. Mohiuddine (Journal of Mathematics)
We use the new variant of Szász–Mirakjan operators to construct a generalized version of Szász-beta type operators and obtain auxiliary lemmas. We present the weighted approximation theorems and, by using Peetre’s K-function, the local approximation results of these operators are studied. We also analyze the rate of convergence by utilizing Lipschitz-type maximal functions and the ordinary modulus of continuity. Moreover, using aforesaid operators, we finally examine the Voronovskaya-type theorem.